Event-Related Potentials during Verbal Recognition of Naturalistic Neutral-to-Emotional Dynamic Facial Expressions - Vladimir Kosonogov; Ekaterina Kovsh; Elena Vorobyeva (Applied Sciences, 2022)
Event-related potentials during facial emotion recognition have been studied for more than twenty years. Nowadays, there has been a growing interest in the use of naturalistic stimuli. This research was aimed, therefore, at studying event-related potentials (ERP) during recognition of dynamic facial neutral-to-emotional expressions, more ecologically valid than static faces. We recorded the ERP of 112 participants who watched 144 dynamic morphs depicting a gradual change from a neutral expression to a basic emotional expression (anger, disgust, fear, happiness, sadness and surprise) and labelled those emotions verbally. We revealed some typical ERP, like N170, P2, EPN and LPP. Participants with lower accuracy exhibited a larger posterior P2. Participants with faster correct responses exhibited a larger amplitude of P2 and LPP. We also conducted a classification analysis that yielded the accuracy of 76% for prediction of participants who recognise emotions quickly on the basis of the amplitude of posterior P2 and LPP. These results extend data from previous research about the electroencephalographic correlates of facial emotion recognition.